A review of the economic and social condition of Ireland - Todhunter, Joseph (Statistical and Social Inquiry Society of Ireland, 1899)
Several of my predecessors in the office of President have taken as the subject-matter of their addresses a review of the economic and social condition of Ireland as revealed to us in the statistics furnished by the General Register Office, and by other Departments of Government. That I should follow their example may, perhaps, be considered appropriate, seeing that the fiftieth anniversary of the foundation of this Society has passed during my term of office. I do not propose to travel over the whole field of Irish statistics, nor would it be desirable that I should do so. After the Census of 1881 and of 1891, Dr. Grimshaw, the Registrar General, gave us most valuable addresses, in which he dealt with great ability, and in the most comprehensive manner with the wide range of statistical records with which his important office is conversant. I desire to draw your attention only to some particular branches of enquiry, regarding which I purpose making some observations as the figures pass under review.
Read Tuesday, June 27th, 1899
Keywords: Emigration; Agricultural production; Export market; Transport infrastructure; 314.15